Aloe Extracellular Vesicles as Carriers of Photoinducible Metabolites Exhibiting Cellular Phototoxicity - Eleonora Calzoni; Agnese Bertoldi; Alessio Cesaretti; Husam B. R. Alabed; Giada Cerrotti; Roberto Maria Pellegrino; Sandra Buratta; Lorena Urbanelli; Carla Emiliani (Cells)
The growing interest in plant-origin active molecules with medicinal properties has led to a revaluation of plants in the pharmaceutical field. Plant-derived extracellular vesicles (PDEVs) have emerged as promising candidates for next-generation drug delivery systems due to their ability to concentrate and deliver a plethora of bioactive molecules. These bilayer membranous vesicles, whose diameter ranges from 30 to 1000 nm, are released by different cell types and play a crucial role in cross-kingdom communication between plants and humans. Notably, PDEVs have demonstrated efficacy in treating various diseases, including cancer, alcoholic liver disease, and inflammatory bowel disease. However, further research on plant vesicles is necessary to fully understand their traits and purposes. This study investigates the phototoxic effects of extracellular vesicles (EVs) from Aloe arborescens, Aloe barbadensis, and Aloe chinensis on the human melanoma cell line SK-MEL-5, focusing on their anthraquinone content, recognized as natural photosensitizers. The phototoxic impact of Aloe EVs is associated with ROS production, leading to significant oxidative stress in melanoma cells, as validated by a metabolome analysis. These findings suggest that EVs from Aloe arborescens, Aloe barbadensis, and Aloe chinensis hold promise as potential photosensitizers, thus highlighting their potential for future application in photodynamic cancer therapy and providing valuable insights into the possible utilization of PDEVs for therapeutic purposes.